Human capital measurement, ambiguity, and opportunism: Actors between menace and opportunity - Gotthard Pietsch (Zeitschrift für Personalforschung (ZfP), 2007)
Under the growing influence of economic normative thoughts (as for example the spread of shareholder value philosophy in the 1990s) and therefore under pressure to justify themselves, human resource management professionals are searching for concepts to measure the effects of their decisions and activities on business objectives. Especially, the concepts of human capital measurement attract far-reaching attention. However, that performance measurement of human resource management faces considerable methodical problems leading to the distinctive ambiguity of human capital information. In the face of this ambiguity, the paper points out that human capital measurement tends to promote opportunistic patterns of behavior by offering opportunities to evade personal responsibility. Referring to the model of organizational anarchy, the paper shows that human capital measurement is in danger to evoke a dilution of responsibilities in organizations. But a comprehensive institutionalization and a deliberate 'framing' of human capital measurement can contribute to the limitation of opportunism.
Keywords: 330; human capital measurement; opportunism; organizational anarchy; value based management; Humanvermögen; Shareholder Value; Verantwortung; Opportunismus